Perineural and Intra-neural Invasion in Posttherapy Pancreaticoduodenectomy Specimens Predicts Poor Prognosis in Patients with Pancreatic Ductal Adenocarcinoma - Chatterjee, Deyali (2012)
Perineural invasion (PNI) is one of the established prognostic factors in pancreatic ductal adenocarcinoma (PDAC). However, the prognostic significance of PNI in patients with PDAC who received neoadjuvant therapy and pancreaticoduodenectomy (PD) is not clear. In this study, we performed detailed examination of neural invasion in PD specimens from 212 patients with PDAC who received neoadjuvant chemoradiation (treated group) and 60 untreated patients at our institution between January 1999 and December 2007. The frequency of PNI was higher in untreated group (80%, 48/60) than the treated group (58%, 123/212). For the 123 treated cases that were positive for PNI, extra-tumoral PNI, intra-tumoral PNI, intra-pancreatic PNI only, extra-pancreatic PNI, and intra-neural invasion were identified in 86 (69.9%), 37 (30.1%), 11 (8.9%), 112 (91.1%), and 35 (28.5%) respectively. Presence of PNI correlated with tumor size, margin status, lymph node metastasis, pathologic tumor and AJCC stages in the treated group. Tumor involvement of nerves >0.8 mm correlated with higher frequency of positive margin compared to those with PNI involving nerves ≤0.8 mm, but not with other clinicopathologic parameters and survival. In treated group, the presence of PNI or intra-neural invasion correlated significantly with shorter disease-free survival (DFS) and overall survival (OS) compared to those with no PNI or PNI only respectively. PNI was an independent prognostic factor for both DFS and OS in multivariate analysis. Our results showed that PNI plays an important role in the progression of PDAC and in predicting the prognosis in this group of patients.